Energy Issues in Germany Kazakhstan Relations - Biturayev Uktamjon Bazarbayevich (Scientific Trends, 2025)
Due to the long-term economic sanctions between the European Union and Russia, the issue of the formation of a promising German-Russian energy policy has entered the crisis street, and the hope for its revival is diminishing. The conflicting Russian-German relations in the period leading up to Russia’s invasion of Ukraine in 2022, violating its territorial integrity, were heavily influenced by the idea of what is known in the literature as “change through rapprochement.” This way of thinking not only survived communism, but also continued in Germany's reunification policy towards post-communist Russia. The idea that geopolitical rapprochement and the development of economic relations can lead to positive change has persisted since the 1970s.